1985
DOI: 10.1111/j.1751-0813.1985.tb14146.x
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective study of head fractures in 21 horses

Abstract: The clinical features of 21 horses which sustained head fractures are reviewed. There was a higher incidence of fractures in males and Standardbred horses. Surgical treatment was practical and successful in most cases when the fractures involved the bones of the jaws and the face. Fractures which involved the cranial cavity or the cranial nerves were difficult to treat and usually held a poor prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 2 publications
0
23
0
1
Order By: Relevance
“…Similarly, Weller et al 3 reported a case where maxillary fracture/sequestrum was detected by scintigraphy but not radiography. Radiographic changes associated with skull trauma are reportedly variable and several oblique projections may be required to demonstrate the bony injury 1,25,26 . Non‐displaced fractures are often particularly difficult to detect radiographically.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Weller et al 3 reported a case where maxillary fracture/sequestrum was detected by scintigraphy but not radiography. Radiographic changes associated with skull trauma are reportedly variable and several oblique projections may be required to demonstrate the bony injury 1,25,26 . Non‐displaced fractures are often particularly difficult to detect radiographically.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic changes associated with skull trauma are reportedly variable and several oblique projections may be required to demonstrate the bony injury. 1,25,26 Nondisplaced fractures are often particularly difficult to detect radiographically. Superimposition of soft tissue opacities or fluid lines within the sinuses because of hemorrhage and mucosal inflammation within the sinus may further obscure fracture lines.…”
Section: Bone Sequestra and Fracturementioning
confidence: 99%
“…Repair of rostral mandibular fractures and long oblique fractures of the interdental space has been reported with cortical lag screw fixation (DeBowes et al 1981;DeBowes 1996). Use of dynamic compression plates (DCP) for fixation of fractures through the cheek teeth and spanning the interdental space has also been described (Murch 1980;Little et al 1985). Wallace (1971) described internal fixation with threaded intramedullary (IM) Steinmann pins.…”
Section: Introductionmentioning
confidence: 99%
“…The mandible is quoted as the bone most frequently involved in equine head fractures (Moller and Dollar 1906; Little et al 1985). Fractures are usually traumatic e.g.…”
Section: Mandibular Fracturesmentioning
confidence: 99%